Myocardial Protection by Glucose–Insulin–Potassium in Moderate- to High-Risk Patients Undergoing Elective On-Pump Cardiac Surgery: A Randomized Controlled Trial. (April 2018) - Ellenberger, Christoph; Sologashvili, Tornike; Kreienbühl, Lukas; Cikirikcioglu, Mustafa; Diaper, John; Licker, Marc
Abstract : BACKGROUND: Low cardiac output syndrome is a main cause of death after cardiac surgery. We sought to assess the impact of glucose–insulin–potassium (GIK) to enhance myocardial protection in moderate- to high-risk patients undergoing on-pump heart surgery. METHODS: A randomized controlled trial was performed in adult patients (Bernstein–Parsonnet score >7) scheduled for elective aortic valve replacement and/or coronary artery bypass surgery. Patients were randomized to GIK (20 IU of insulin, 10 mEq of potassium chloride in 50 mL of glucose 40%) or saline infusion given over 60 minutes on anesthetic induction. The primary end point was postcardiotomy ventricular dysfunction (PCVD), defined as new/worsening left ventricular dysfunction requiring inotropic support (≥120 minutes). Secondary end points were the intraoperative changes in left ventricular function as assessed by transoesophageal echocardiography, postoperative troponin levels, cardiovascular and respiratory complications, and intensive care unit and hospital length of stay. RESULTS: From 224 randomized patients, 222 were analyzed (112 and 110 in the placebo and GIK groups, respectively). GIK pretreatment was associated with a reduced occurrence of PCVD (risk ratio [RR], 0.41; 95% confidence interval [CI], 0.25–0.66). In GIK-treated patients, the left systolic ventricular function was better preserved after weaning from bypass, plasma troponin levels were lower on the first postoperative day (2.9 ng·mL −1 [interquartile range IQR, 1.5–6.6] vs 4.3 ng·mL −1 [IQR, 2.4–8.2]), and cardiovascular (RR, 0.69; 95% CI, 0.50–0.89) and respiratory complications (RR, 0.5; 95% CI, 0.38–0.74) were reduced, along with a shorter length of stay in intensive care unit (3 days [IQR, 2–4] vs 3.5 days [IQR, 2–7]) and in hospital (14 days [IQR, 11–18.5] vs 16 days [IQR, 12.5–23.5]), compared with placebo-treated patients. CONCLUSIONS: GIK pretreatment was shown to attenuate PCVD and to improve clinical outcome in moderate- to high-risk patients undergoing on-pump cardiac surgery.